The Greely Arctic expedition as fully narrated by Lieut. Greely, U.S.A., and other survivors. Full account of the terrible sufferings on the ice . - Barclay, George L. (George Lippard), 1849 or 1850-1886. (Philadelphia, Pa., Barclay & co., 1884)
1 p. l., 19-96 p. incl. plates, ports.